2015
DOI: 10.1038/ncomms8247
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of corticobasal degeneration identifies risk variants shared with progressive supranuclear palsy

Abstract: Corticobasal degeneration (CBD) is a neurodegenerative disorder affecting movement and cognition, definitively diagnosed only at autopsy. Here we conduct a GWAS in CBD cases (n = 152) and 3,311 controls, and 67 CBD cases and 439 controls in a replication stage. Associations with meta-analysis were 17q21 at MAPT (P = 1.42 × 10−12), 8p12 at lnc-KIF13B-1, a long non-coding RNA (rs643472; P = 3.41 × 10−8), and 2p22 at SOS1 (rs963731; P = 1.76 × 10−7). Testing for association of CBD with top PSP GWAS SNPs identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
153
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(166 citation statements)
references
References 38 publications
9
153
2
2
Order By: Relevance
“…16,20 However, rs242557 was not associated with the risk of AD (p 5 0.974), 21 which is pathologically characterized by intracellular neurofibrillary tangles composed of roughly equal ratios of 3-and 4-repeat tau. 1 The mechanism by which the MAPT H1c haplotype could increase plasma tau levels is not clear.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…16,20 However, rs242557 was not associated with the risk of AD (p 5 0.974), 21 which is pathologically characterized by intracellular neurofibrillary tangles composed of roughly equal ratios of 3-and 4-repeat tau. 1 The mechanism by which the MAPT H1c haplotype could increase plasma tau levels is not clear.…”
mentioning
confidence: 98%
“…13,14 Genetic studies, including GWAS, have identified both the inversion polymorphism and haplotype-specific polymorphisms influencing the risk of 4-repeat tauopathies (PSP and CBD). 12,13,[15][16][17][18][19] Moreover, the common subhaplotype H1c (tagged by rs242557) on the background of the H1 haplotype has been consistently found to be associated with both PSP and CBD. 12,15,16,20 Previously published GWAS data with neuropathologically diagnosed cases showed that rs242557, tagging the MAPT H1c haplotype, was one of the most common SNPs associated Figure 3 Plasma tau levels in a replication cohort as a function of rs242557 genotype Plasma tau levels were compared across the GG, GA, and AA genotypes of rs242557 in an independent cohort of 387 participants to validate the initially observed association.…”
mentioning
confidence: 99%
“…These results suggest that a panel of SNPs is a potential prognostic biomarker in ApoE4-negative MCI patients (Sun et al 2015). Furthermore, from a genetic point of view, Gunter Hoglinger showed that the tau encoding gene MAPT, is the major risk gene for PSP (Hoglinger et al 2011) and CBD (Kouri et al 2015).…”
Section: Cerebrospinal Fluid (Csf) Sampling With Emphasis On Tau Fragmentioning
confidence: 89%
“…html), we are now ideally positioned to discuss advances and future projections for tau diagnostics and clinical trials. This short review presents our own perspectives, trying to portray an objective view (Gozes 2002;Matsuoka et al 2007;VulihShultzman et al 2007;Matsuoka et al 2008;Shiryaev et al 2009;Gozes 2010aGozes , 2010bKnake et al 2010;Shiryaev et al 2010;Stamelou et al 2010;Gozes 2011;Hoglinger et al 2011;Idan-Feldman et al 2012;Jouroukhin et al 2012;Jouroukhin et al 2013;Boxer et al 2014;Gozes et al 2014;Hoglinger et al 2014;Magen et al 2014;Schirer et al 2014;Tolosa et al 2014;Kouri et al 2015, Sun et al 2015, Levin et al 2016, Stamelou and Hoglinger 2016Boxer et al 2017;Gozes 2017;Hansson et al 2017;Hoglinger et al 2017;Hoglund et al 2017;Respondek et al 2017). …”
Section: Introductionmentioning
confidence: 99%
“…Finally, along with morphological and biochemical studies, the genetic basis of tauopathies is also relevant. The H1 haplotype and the H1c sub-haplotype of the MAPT gene are overrepresented in CBD and PSP, and are thus considered possible risk factors 32 . In addition, genome-wide studies have looked at other potential susceptibility loci, such as 3p22 myelin-associated oligodendrocyte basic protein 31 .…”
Section: Neuropathology and Pathogenic Mechanismsmentioning
confidence: 99%